Economic valuation of ecosystem services in southwest Spain - Esteban Otto Thomasz; Andrés Kasanzew; Agustín García García (Discover Sustainability)
Abstract Extremadura, located in the southwest of Spain, is a region of high natural value, supporting high levels of biodiversity and ecosystem services. However, there is no comprehensive study that estimates the extent to which ecosystem services contribute to the main economic activities of the region. In this context, the aim of this paper is to provide a comprehensive economic estimation of the ecosystem services provided to the most important economic sectors in Extremadura (agriculture, livestock, forest, and recreational services). Different estimation methods were used given the variety of sectors involved, involving the direct market valuation, residual approach, replacement cost, travel expenditure, among others. The results show that the ecosystem services that have a direct impact on production levels represent 7.35% of the regional gross domestic product and 55% of the gross economic value of the related activities representing the potential production loss in the absence of these ecosystem services. This shows a great dependence of some economic activities on natural assets, of which the most important are the water used for irrigation, the Iberian breed, pollination, and grass for livestock. The economic valuation of ecosystem services is fundamental to sustainable development regional strategies.